Análisis comparativo de los costos de producción, productiva y rendimiento del cacao ccn-51 con manejo semitecnificado en dos haciendas seleccionadas en la zona de Quevedo y Balzar. - Alvarado Urina, Carlos Alberto (2013)
The present work of investigation I realize in two household tasks located in different provinces of the Ecuador, the estate Clemency located in the canton Balzar, province of the Guayas and the estate Pretty High Rio located in the province of The Rivers, both property of the Agricultural Industrial Tropical company S.A. Agrotropical. The same one who devotes itself to the production and marketing cocoa ccn-51. The principal aim of this investigation was to evaluate the costs of production, yield and the productivity of the culture of cocoa CCN-51 and hereby to be able to establish the maximum levels of production in each of the household tasks. The raised hypothesis was " The implementation of the culture of cocoa CCN-51 in the zones of Balzar and Quevedo generates high productivity and economic profitability ". The obtaining of the results of this investigation was given by means of the direct investigation; he interviews the owner, personnel of plant and field, and the direct observation of the way. The Estate Pretty High Rio presented during the epoch of the major winter quantity of (mm/ha) what might have helped to obtain major yield, it is necessary to emphasize that we can use this natural factor to highlight that it could have generated major productivity but also to be able stop happen for high that this estate in the labor of fungicides and insecticides presented major cost surely the spread of plagues, insects and fungi they re-produced in major scale due to the conditions climatic that was big enough in the winter epoch, whereas though it is true in the estate A Clemency they registered minor quantity of (mm/ha) during the period of study but of equal way the use of fungicides and insecticides was low in this estate. In the control of undergrowths, the estate Pretty High Rio registered minor effect of bad grasses, since there was demonstrated the minor consumption of herbicide and manpower. Whereas the estate Clemency registered major presence of undergrowths, which produced a major cost principally in the record of manpower. In the labor of pruning the estate Clemency assessed the minor cost this wants to say that in this estate it existed minor attends of foliage or in turn that the type of pruning realized in this estate was less drastic in comparison to the estate Pretty Rio due High place that in this estate the cost was top both in manpower and in used inputs, and it is necessary to stress that this labor I represent 10 % of the Changeable costs. In the activity of fertilization, the estate Clemency generated the major cost of inputs and of manpower nevertheless this was not reflected in major yields of boxes for hectare, possibly for an inadequate managing of the fertilizer in the plantation. Whereas the estate Pretty High Rio obtained the minor cost and besides the highest yield of conscript them for hectare. The fertilization represented less than 25 % of the changeable cost in this estate. Once obtained the resultado there was demonstrated that the estate Pretty High Rio is much more profitable than the estate Clemency provided that the high levels of production help to that this estate is one of the producting mas for the company Agrotropical, and that in spite of handling major costs of production in comparison to the estate Clemency generates major profitability.